SMART WAY OF GENERATING ELECTRICITY IN METRO POLITIAN CITIES - Gandhi, Kapil; Dwivedi, Ashutosh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
This present paper seek to generate the electricity in the metro Politian cities by using vertical axis wind turbine at height of 150 meter from the ground which situated at the top of the building.